The impact of environmental regulation or bargaining power on green total factor productivity: Evidence from Taiwan-funded enterprises in Chinese mainland - Huang, Yanping; Li, Xiapei; Liu, Yu (Frontiers in Environmental Science, 2022)
Energy conservation and emission reduction of the manufacturing industry are of great significance for promoting China's high-quality economic development. In this paper, the Luenberger productivity index based on the data envelopment analysis (DEA) method is used to measure the green total factor productivity (GTFP). The regression results show that, on the one hand, environmental regulation on Taiwan-funded enterprises has a negative impact on the GTFP, which implies that these enterprises need to pay "compliance costs" due to the implementation of environmental regulation policies of Chinese local governments. On the other hand, Taiwan-funded enterprises who can create a large number of jobs have strong bargaining power with the local governments, hence have more opportunities to be exempted from environmental regulations to a certain extent. Therefore, in order to prevent local governments from failing to strictly implementing environmental regulations on Taiwan-funded enterprises, it is suggested that environmental protection achievements be included in the performance appraisal system for the local governments. Chinese local governments should start with a weaker enforcement of environmental regulation, by giving Taiwan-funded enterprises a certain buffer period to gradually adjust the policies intensity. Production characteristics and pollution density of Taiwan-funded enterprises should be considered when enforcing environmental regulation. It is also suggested that environmental, social and governance (ESG) scores of Taiwan-funded enterprises should be taken as a part of their credit qualifications, so as to enhance the internal motivation of energy conservation and emission reduction of these enterprises. In this way, environmental regulation will play a full role in promoting the GTFP of Taiwan-funded enterprises, and help the high-quality development of Chinese economy.